Expansionary Yet Different: Credit Supply and Real Effects of Negative Interest Rate Policy - Margherita Bottero; Camelia Minoiu; José-Luis Peydró; Andrea Polo; Andrea Presbitero; Enrico Sette (ZBW – Leibniz Information Centre for Economics, 2020)
We show that negative interest rate policy (NIRP) has expansionary effects on bank credit supply and firm outcomes through a portfolio rebalancing channel. For identification, we exploit ECB's NIRP and credit register, firm- and bank-level datasets. NIRP affects relatively more banks with higher ex-ante net interbank positions or more liquid balance sheets. More exposed banks reduce liquid assets, expand credit supply to ex-ante riskier firms, and cut rates, inducing sizable firm-level real effects. By shifting down and flattening the yield curve, NIRP differs from rate cuts just above the zero-lower-bound. We find no evidence of a contractionary retail deposit channel.
Keywords: G01; G21; G28; E52; E58; 330; negative nominal interest rates; firm-level real effects; Eurozone crisis; portfolio rebalancing; liquidity management